Analisis terhadap Pengajaran Pendidikan Agama Katolik kepada Mahasiswa - Fransiska Romana Wuriningsih; Gregorius Daru Wijoyoko (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2022)
The first objective of this study is to evaluate in depth of the teaching implementation on Catholic Education toward students in Semarang. The second objective is to determine the factors of success either failure of teaching Catholic education to students in Semarang. The research method used is the Research and Development method. The researcher acts as an analyst of research subjects who are involved in the teaching and learning process of Catholic Education in campus. The results of the study revealed that firstly, in order to optimally implement Catholic Education, it is necessary to improve internal quality (quality of the close relationship between lecturers/students with God, readiness to learn and teach, deepening of theological knowledge, emotional intelligence, easy-to-understand language, self-control) carried out by lecturers and students during learning. Secondly, Moreover, there needs to be an improvement in external quality (applying PAK values ​​to a plural society). Thirdly, it is necessary to improve the module by integrating the values ​​of evangelical joy.